Role of Learning Ability and Learning Agility for Corporate Success : A Textual Analysis - Vatsa, Ruchika; Bhatnagar, Purnima (Prabandhan: Indian Journal of Management, 2021)
Learning agility has been considered an essential antecedent in the context of organizational performance in recent years. The present study aimed to review selected papers for the association between learning agility and learning ability at an individual and an organizational level. Textual analysis was done to extract the word count, word occurrence, similarity, and clustering from 29 research papers. An open-source predictive analytics platform software RapidMiner Studio 9.6 version was utilized. This software permitted different operators of Natural Language Programming (NLP), R, and K-means algorithms to analyze the data, and 9,034 words attributes were observed to exist in the database, and the word â€œLearnâ€ occurred 3,382 times in it. Similarity analysis yielded two files to be a 100% match since both used a systems modeling framework. The thematic analysis generated 25 words through the Latent Dirichlet allocation operator. Cluster analysis highlighted five groups, out of which one of the clusters with eight papers was observed as having similar content. This meant that the authors were discussing a similar perspective in these studies. The paper is innovative in being one of the first to use RapidMiner software in the discussion regarding learning agility and learning ability. The analysis methods used in this paper provide an insight into variables required for an agile workplace. These variables may be utilized to develop a conceptual framework model for an organizationâ€™s agile learning and development initiatives.